Postoperative surveillance of pancreatic cancer patients. Issue 10 (October 2019) - Daamen, L.A.; Groot, V.P.; Intven, M.P.W.; Besselink, M.G.; Busch, O.R.; Koerkamp, B. Groot; Mohammad, N. Haj; Hermans, J.J.; van Laarhoven, H.W.M.; Nuyttens, J.J.; Wilmink, J.W.; van Santvoort, H.C.; et al.
Abstract: Background: The aim of this study is to collect the best available evidence for diagnostic modalities, frequency, and duration of surveillance after resection for pancreatic ductal adenocarcinoma (PDAC). Methods: PDAC guidelines published after 2015 were collected. Furthermore, a systematic search of the literature on postoperative surveillance was performed in PubMed and Embase from 2000 to 2019. Articles comparing different diagnostic modalities and frequencies of postoperative surveillance in PDAC patients with regard to survival, quality of life, morbidity and cost-effectiveness were selected. Results: The literature search resulted in 570 articles. A total of seven guidelines and twelve original clinical studies were eventually evaluated. PDAC guidelines increasingly recommend a combination of tumor marker testing and computed tomography (CT) imaging every three to six months during the first two years after resection. These guidelines are, however, based on expert opinion and other low-level evidence. Prospective studies comparing different surveillance strategies are lacking. According to recent studies, surveillance with tumor markers and imaging at regular intervals results in the detection of PDAC recurrence before the onset of symptoms and more frequent administration of further therapy, such as chemotherapy or radiotherapy. Conclusion: Current evidence for recurrence-focused surveillance after PDAC resection is limited and contradictory. Consequently, recommendations on surveillance are conflicting. To define the clinical merit of recurrence-focused surveillance, patients who are most likely to benefit from early detection and treatment of PDAC recurrence need to be identified. To this purpose, well-designed prospective studies are needed, accounting for both economical and psychosocial implications of surveillance.